The OEIS Foundation is supported by donations from users of the OEIS and by a grant from the Simons Foundation.

 Hints (Greetings from The On-Line Encyclopedia of Integer Sequences!)
 A038725 a(n) = 6*a(n-1) - a(n-2), n >= 2, a(0)=1, a(1)=2. 12
 1, 2, 11, 64, 373, 2174, 12671, 73852, 430441, 2508794, 14622323, 85225144, 496728541, 2895146102, 16874148071, 98349742324, 573224305873, 3340996092914, 19472752251611, 113495517416752, 661500352248901 (list; graph; refs; listen; history; text; internal format)
 OFFSET 0,2 COMMENTS From Wolfdieter Lang, Feb 26 2015: (Start) The sequence {2*a(n+1)}_{n >= 0}, gives all positive solutions y = y2(n) = 2*a(n+1) of the second class of the Pell equation x^2 - 2*y^2  = -7. For the corresponding terms x = x2(n) see A255236(n). See A255236 for comments on the first class solutions and the relation to the Pell equation x^2 - 2*y^2 = 14. (End) REFERENCES A. H. Beiler, Recreations in the Theory of Numbers, Dover, N.Y., 1964, pp. 122-125, 194-196. LINKS I. Adler, Three Diophantine equations - Part II, Fib. Quart., 7 (1969), pp. 181-193. Seyed Hassan Alavi, Ashraf Daneshkhah, Cheryl E Praeger, Symmetries of biplanes, arXiv:2004.04535 [math.GR], 2020. See x'(n) in Lemma 7.9 p. 21. E. I. Emerson, Recurrent Sequences in the Equation DQ^2=R^2+N, Fib. Quart., 7 (1969), pp. 231-242. Tanya Khovanova, Recursive Sequences Index entries for linear recurrences with constant coefficients, signature (6,-1). FORMULA a(n) = 7*a(n-1) - 7*a(n-2) + a(n-3); a(n) = ((4-sqrt(2))/8)*(3+2*sqrt(2))^(n-1)+((4+sqrt(2))/8)*(3-2*sqrt(2))^(n-1). - Antonio Alberto Olivares, Mar 29 2008 Sequence satisfies -7 = f(a(n), a(n+1)) where f(u, v) = u^2 + v^2 - 6*u*v. - Michael Somos, Sep 28 2008 G.f.: (1 - 4*x) / (1 - 6*x + x^2). a(n) = (7 + a(n-1)^2) / a(n-2). - Michael Somos, Sep 28 2008 From Wolfdieter Lang, Feb 26 2015: (Start) a(n) = S(n, 6) - 4*S(n-1, 6), n>=0, with the Chebyshev polynomials S(n, x) (A049310), with S(-1, x) = 0, evaluated at x = 6. S(n, 6) = A001109(n-1). See the g.f. and the Pell equation comment above. a(n) = 6*a(n-1) - a(n-2), n >= 1, a(-1) = 4, a(0) = 1. (See the name.) (End) From Wolfdieter Lang, Mar 19 2015: (Start) a(n+1) = sqrt((A255236(n)^2 + 7)/2)/2, n >= 0. a(n+1) = (A038761(n) + A038762(n))/2, n >= 0. See the Mar 19 2015 comment on A054490. - Wolfdieter Lang, Mar 19 2015 E.g.f.: exp(3*x)*(4*cosh(2*sqrt(2)*x) - sqrt(2)*sinh(2*sqrt(2)*x))/4. - Stefano Spezia, May 01 2020 EXAMPLE n = 2: a(3) = sqrt((181^2 + 7)/2)/2 = 64. a(3) = (53 + 75)/2 = 64. - Wolfdieter Lang, Mar 19 2015 MAPLE a[0]:=1: a[1]:=2: for n from 2 to 26 do a[n]:=6*a[n-1]-a[n-2] od: seq(a[n], n=0..20); # Zerinvary Lajos, Jul 26 2006 MATHEMATICA Union[Flatten[NestList[{#[[2]], #[[3]], 6#[[3]]-#[[2]]}&, {1, 2, 11}, 25]]]  (* Harvey P. Dale, Mar 04 2011 *) LinearRecurrence[{6, -1}, {1, 2}, 30] (* Harvey P. Dale, Jun 12 2017 *) PROG (PARI) {a(n) = real((3 + 2*quadgen(8))^n * (1 - quadgen(8) / 4))} /* Michael Somos, Sep 28 2008 */ (PARI) {a(n) = polchebyshev(n, 1, 3) - polchebyshev(n-1, 2, 3)} /* Michael Somos, Sep 28 2008 */ CROSSREFS Cf. A001653 and A001541. Cf. A001109. A038723(n) = a(-n). Sequence in context: A080049 A126745 A179120 * A161947 A001565 A199412 Adjacent sequences:  A038722 A038723 A038724 * A038726 A038727 A038728 KEYWORD easy,nonn AUTHOR Barry E. Williams, May 02 2000 STATUS approved

Lookup | Welcome | Wiki | Register | Music | Plot 2 | Demos | Index | Browse | More | WebCam
Contribute new seq. or comment | Format | Style Sheet | Transforms | Superseeker | Recent
The OEIS Community | Maintained by The OEIS Foundation Inc.

Last modified October 20 23:28 EDT 2020. Contains 337910 sequences. (Running on oeis4.)